2017
DOI: 10.1007/s00066-017-1212-z
|View full text |Cite
|
Sign up to set email alerts
|

Air–electron stream interactions during magnetic resonance IGRT

Abstract: During radiotherapy for breast cancer with an MR-IGRT system, the patient must be shielded from electron streams in the air generated by the interaction of the magnetic field with the beams of the three-cobalt treatment unit to avoid unwanted irradiation of the skin outside the treatment field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 21 publications
1
76
3
Order By: Relevance
“…Furthermore, the MR‐linac delivers beams from multiple gantry angles during a treatment, and several gantry orientations, particularly posterior–anterior beams, will have a minimal SCE dose contribution. Park et al . observed recently isodose contours of as much as 15% of the prescription dose streaming away from the treatment area and in the direction of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the MR‐linac delivers beams from multiple gantry angles during a treatment, and several gantry orientations, particularly posterior–anterior beams, will have a minimal SCE dose contribution. Park et al . observed recently isodose contours of as much as 15% of the prescription dose streaming away from the treatment area and in the direction of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the MR-linac delivers beams from multiple gantry angles during a treatment, and several gantry orientations, particularly posterior-anterior beams, will have a minimal SCE dose contribution. Park et al 27 observed recently isodose contours of as much as 15% of the prescription dose streaming away from the treatment area and in the direction of the magnetic field. Considering that the air-generated SCE dose contribution is on the order of about 5% as shown by Hackett et al, this would indicate that further work is required into investigating the contribution of in-patient generated electron to out-of-field doses.…”
Section: Resultsmentioning
confidence: 99%
“…The second effect that should be kept in mind for breast cancer treatment on a hybrid machine is the ESE in air, which can lead to dose being deposited in tissues well outside the irradiated field (Figure 4). This was first observed and evaluated by Park et al (64), who, in the context of accelerated PBI delivered on the 0.35 T 60 Co ViewRay system, observed an electron stream in air extending toward the head and ipsilateral arm. This ESE is caused by electrons generated inside the body that, instead of scattering in random directions when leaving the body, start spiraling along the magnetic field (65).…”
Section: Electron Stream Effectmentioning
confidence: 74%
“…If unobstructed, this electron stream would reach the chin and arm, causing unwanted irradiation of the skin in these areas. In an extreme case, the maximum dose measured was as high as 16.1% of the prescribed dose (64). Dose to the skin outside the treatment field was highest in patients with tumours located in the cranial part of the breast.…”
Section: Electron Stream Effectmentioning
confidence: 91%
See 1 more Smart Citation